5(x-5)-6x=-2

Simple and best practice solution for 5(x-5)-6x=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-5)-6x=-2 equation:


Simplifying
5(x + -5) + -6x = -2

Reorder the terms:
5(-5 + x) + -6x = -2
(-5 * 5 + x * 5) + -6x = -2
(-25 + 5x) + -6x = -2

Combine like terms: 5x + -6x = -1x
-25 + -1x = -2

Solving
-25 + -1x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '25' to each side of the equation.
-25 + 25 + -1x = -2 + 25

Combine like terms: -25 + 25 = 0
0 + -1x = -2 + 25
-1x = -2 + 25

Combine like terms: -2 + 25 = 23
-1x = 23

Divide each side by '-1'.
x = -23

Simplifying
x = -23

See similar equations:

| 7/12*9/2-33/40 | | (2x^2-6x-8)/(x+1) | | 3s^4+8s^2-2=0 | | 7/x+3-5/x-3=3x/x^2-9 | | 14x^2/7x | | -13+6=m-10 | | 6v^2+3v-4=-4v^2 | | 3a^2-14a-5=0 | | 2v^2+3v-4=0 | | -13+6=m-16 | | y=-1*1 | | 7/12x9/2-33/40 | | 4/5b=120 | | 4/5b=48 | | y=-3/4*1+6 | | -0.75*-3/4x+6 | | x^2+5x-37.5=0 | | 96x^2-204x-99=0 | | 450+0.06s=0.06s+900 | | x-43=0 | | 3(6s+12)-10s-6=0 | | 6*4-4y=-24 | | 15c^2-17c-42=0 | | 6x-4*4=-24 | | x^2-x-169=0 | | 13x+10y=20 | | 44x+7=x | | 3(n)+7=46 | | (1/2)x-15=30 | | 2(x+5)-8= | | =165(2.1)0.09t | | 26x+5y=31 |

Equations solver categories